The Effectiveness of Game-Based Learning Tapak Langkah to Increase Learning Motivation of Elementary School Students - Safitri, Umi Arum; Wulandari, Murfiah Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This quantitative study has the goal of measuring the effectiveness of Tapak Langkah game-based learning to increase learning motivation in elementary school students. Methodology: This study uses the design of the Pree Post Test Control Group. The subject of this study involves 43 students (22 students of class IV A and 21 students of class IV B). Student learning motivation data was collected through ques-tionnaires. The collected data was analyzed using parametric statistical types, namely the General Linear Model test and the N-gain test. Results: The results of the study showed that the General Linear Model test had a sig-nificance value of 0.000 < 0.05. In the N-gain test, a score of 83.9941% of the experimental class and 29.7667% of the control class was obtained, which means that the use of the Tapak Langkah game proved to be effective in increasing the learning motivation of elementary school students. Applications/Originality/Value: The use of the Step Site game in increasing learning motivation has not been researched. Following up on the findings in this study, game-based learning can be explored so that students get the maximum learning experience.